PENGARUH CAPITAL ADEQUANCY RATIO (CAR), BIAYA OPERASI PENDAPATAN OPERASI (BOPO) DAN LOAN DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSETS (ROA) BANK DEVISA DI INDONESIA - Kasyati Kasyati; Suwarno Suwarno; Tjahjani Murdijaningsih (FEB UNWIKU PURWOKERTO, 2020)
The purpose of this study was to analyze the positive significance of the effect of CAR on the Foreign Exchange Bank ROA in Indonesia, to analyze the negative significance of the effect of BOPO on Foreign Exchange Bank ROA in Indonesia and to analyze the positive significance of the LDR on Foreign Exchange Bank ROA in Indonesia. The analytical tool used in this study is multiple linear regression analysis. From this research it can be concluded: (1) The first hypothesis which states CAR has a significant positive effect on the ROA of Foreign Exchange Banks in Indonesia, accepted. This is evidenced by the t test, t calculate CAR greater than t table (2,075> 1,6628), (2) The second hypothesis which states that BOPO has a significant negative effect on the ROA of Foreign Exchange Banks in Indonesia, is accepted. This is evidenced by the t test, -t count BOPO <-t table (-10.455 <- 1,6628), (3) The third hypothesis which states that the LDR has a significant negative effect on the ROA of Foreign Exchange Banks in Indonesia, is rejected. This is evidenced by the t test, -t count LDR> -t table ((-0,915> -1,6628).